Strength, corrosion resistance and cellular response of interfaces in bioresorbable poly-lactic acid/Mg fiber composites for orthopedic applications. (November 2021) - Ali, Wahaaj; Echeverry-Rendón, Mónica; Kopp, Alexander; González, Carlos; LLorca, Javier
Abstract: The shear strength and the corrosion resistance of the fiber/matrix interface after immersion in simulated body fluid was studied in poly-lactic acid/Mg fiber composites. The shear strength of the interface was measured by means of push-out tests in thin slices of the composite perpendicular to the fibers. It was found that the interface strength dropped from 15.2 ± 1.4 MPa to 7.8 ± 3.7 MPa after the composite was immersed in simulated body fluid for 148 h. The reduction of the interface strength was associated to the fast corrosion of the fibers as water diffused to the interface through the polymer. The expansion of the fibers due to the formation of corrosion products was enough to promote radial cracks in the polymer matrix which facilitate the ingress of water and the development of corrosion pitting in the fibers. Moreover, cell culture testing on the material showed that early degradation of the Mg fibers affected the proliferation of pre-osteoblasts near the Mg fibers due to the local changes in the environment produced by the fiber corrosion. Thus, surface modification of Mg fibers to delay degradation seems to be a critical point for further development of Mg/PLA composites for biomedical applications.